Resource partitioning and adequacy among ontogenetic groups in a hermit crab and gastropod shell network - Santos, Mateus Pereira [UNESP]; Rodrigues, Gabriel Fellipe Barros [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP]; Fransozo, Vivian (My University, 2021)
In ecology, interaction networks allow the investigation of how interactions among species affect community structure and functioning. The structure of interaction networks can be nested and/or modular. Ecologically, the nested structure minimizes competition and increases the number of coexisting species, creating high diversity, while the modular structure occurs when there are non-overlapping groups of highly interacting consumer-resource species. Despite the importance of gastropod shells to hermit crabs, currently, few studies explored the structure of hermit crabs communities through a resource-usage perspective. Therefore, network analyses appear as an important tool to unveil how the use of empty shell as a resource rules hermit crabs communities through competition among species and rules hermit crabs populations through competition among distinct ontogenetic groups. This study investigated the resource usage pattern of empty gastropod shells by distinct ontogenetic stages of the hermit crab Calcinus tibicen from two different locations, using a network approach and the “Shell Adequacy Index” (SAI) analysis. The present results show that the interaction network between ontogenetic groups and gastropod shells was non-nested and modular and the SAI reflected the differences between males and ovigerous females in both locations, regarding shell size adequacy. We suggest that the modular structure may be a result of resource partitioning, which, in turn, is favored in habitats with a high degree of heterogeneity. The modular network structure may indicate habitat heterogeneity and resource partitioning. Future studies including other hermit crab species from the same areas should help determine how shells are partitioned interspecifically.
Keywords: Modularity; Nestedness; Paguroidea; Rocky shore; SAI; Shells of gastropods